Modern Quantum Mechanics - Sakurai, J. J.; Napolitano, Jim J. (New Delhi: Pearson India, 2014)
The author, J. J. Sakurai, was a renowned theorist in particle theory. This revision by Jim Napolitano retains the original material and adds topics that extend the texts usefulness into the 21st century. The introduction of new material and modification of existing material, appears in a way that better prepares the student for the next course in quantum field theory. Students will still find such classic developments as neutron interferometer experiments, Feynman path integrals, correlation measurements and Bells inequality. The style and treatment of topics is now more consistent across chapters. The Second Edition has been updated for currency and consistency across all topics and has been checked for the right amount of mathematical rigor.
Appendix A-B 499-512p.; Bibliography 513-514p.; Index 515-520p.